Review of adaptation indicators in Nationally Determined Contributions (NDCs) and National Adaptation Plans (NAPs) in Africa - Nowak, Andreea C. (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Presentation for the AGNES Climate Leadership Training, 05.08.2021